Policy and Ecosystem Pathways to Inclusive Women-Led Digital Venture Growth - Muhammad Abiyan Hilal; Diana Puspitasari (Jurnal Inovasi Pajak Indonesia, 2025)
Purpose – We can determine how sustainable business performance is in a female-led digital entrepreneurship ecosystem by focusing on resource access, digital capabilities, and the socio-institutional context, all at the same time.Design/methodology/approach – The interconnected drivers of resources, barriers, and context in determining sustainable entrepreneurship outcomes are analysed in this manuscript using a structural equation modelling strategy.Findings – The results show that access to financing, ecosystem support, and digital capabilities are important in improving sustainable business performance, whereas gender-based social norms and work-family role pressures act as barriers. The transformation of entrepreneurial resources into performance impacts is further strengthened by institutional trust and policy clarity, with the negative effects of structural barriers being mitigated. At the same time, the positive effects of resources are reinforced by entrepreneurial thinking that is focused on opportunities, while social and role constraints are negated. The interaction between external resources, institutional context, and internal entrepreneurial cognition is suggested as the source of sustainable business performance, rather than isolated determinants.Originality/value – This article contributes to entrepreneurship and sustainability studies by combining feminist, institutional, and digital capability perspectives within an integrated resource–barrier model that explicitly recognises context moderation mechanisms.Research implications – This contribution has implications for forward-looking theory in sustainable and inclusive entrepreneurship. It also has implications for designing policies and support systems. These encourage the development of women-led enterprises in emerging entrepreneurial contexts.